Bright, dark, periodic and kink solitary wave solutions of evolutionary Zoomeron equation - Yao, Shao-Wen; Akram, Ghazala; Sadaf, Maasoomah; Zainab, Iqra; Rezazadeh, Hadi; İnç, Mustafa (Elsevier, 2022)
The modified auxiliary equation (MAE) approach and the generalized projective Riccati equation (GPRE) method are used for the first time to solve Zoomeron problem which provided different types of exact traveling wave solutions, including some new dynamical behaviors. The governing model covers unique examples of solitons with distinct properties that emerge in a variety of physical situations, including laser physics, fluid dynamics and nonlinear optics. The achieved exact traveling wave solutions include solitary wave, periodic wave, bright, dark peakon, and kink-type wave solutions. Earned results are given as hyperbolic and trigonometric functions. Moreover, the dynamical features of obtained results are demonstrated through interesting plots.
Keywords: Nonlinear evolution equations; Zoomeron equation; Modified auxiliary equation method; Generalized projective Riccati equation method; Exact solutions